From knowledge management to strategic competence : measuring technological, market and organisational innovation - Tidd, Joseph, 1960- (Series on technology management ;, 2000)
The business and academic communities pay much interest to the concept of knowledge management and strategic competencies or core capabilities; that is, how organizations define and differentiate themselves. This book attempts to establish the links between strategic competencies, knowledge management, organizational learning and innovation management - specifically, how an organization identifies, assesses and exploits its competencies, and translates these into new processes, products and services. The contributors to the book include leading researchers and consultants in the field. Adopting a practical but rigorous approach to the subject, they focus on the measurement, management and improvement of organizational, technological and market competencies, and identify the relationships with strategic, operational and financial performance.